Prawidłowość wdrożenia dyrektywy 2008/48/WE z dnia 23 kwietnia 2008 roku w zakresie krajowej regulacji limitu pozaodsetkowych kosztów kredytowych — prawne aspekty problemu - Wiltosiński, Konrad (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The following article attempts to analyze Articles 36a–36d of the Act on Consumer Credits, recently introduced into Polish legislation. The author of the article defends the view that legal regulations, as adopted by the national legislator, have been afalse attempt to implement Directive 2008/48/EC in the national legal order, as they allow for aclassification of entrepreneurs’ business overhead costs as costs related to credit agreements to be borne by consumers. Furthermore, the following paper aims at presenting, in asynthetic way, the main trends represented in the case-re-lated doctrine and judicial decisions
Keywords: consumer protection; approximation of laws; maximum non-interest credit costs; consumer loan